Influence Party Funds Third and Profit Sharing Financing to Jambi Syariah Bank Assets: Empirical Data 2015 – 2025 - Rosiqo Rosiqo; Nourita Nourita; Sri Mawarni; Nurwidayani Dani; Yeni Anggraini; M. Yunus (International Journal of Economics and Management Research, 2025)
This study aims to analyze the effect of third-party funds (TPF) and profit-sharing financing on the assets of Bank Jambi Syariah. Assets are a key indicator in assessing the financial capacity and performance of Bank Jambi Syariah. The research uses monthly time series data over a three-year period and applies multiple linear regression analysis. The results show that both TPF and profit-sharing financing have a significant positive effect on UUS assets. The positive influence of TPF indicates that increased public fund collection can strengthen the financial structure of Islamic business units. Likewise, profit-sharing financing significantly contributes to asset growth, reflecting the effectiveness of fund distribution through productive partnerships. Classical assumption tests confirm that the regression model satisfies the criteria of normality, homoscedasticity, no autocorrelation, and no multicollinearity. The coefficient of determination (R²) value of 0.7356 indicates that 73.56% of the variation in assets can be explained by TPF and profit-sharing financing. These findings highlight the importance of optimal fund management and financing in supporting the asset growth of Islamic Business Units.